2022
DOI: 10.3390/curroncol29050238
|View full text |Cite
|
Sign up to set email alerts
|

Study of PD-1 Inhibitors in Combination with Chemoradiotherapy/Chemotherapy in Patients with Esophageal Squamous Carcinoma

Abstract: In this study, we aimed to evaluate the efficacy of PD-1 inhibitors in combination with concurrent CRT/CT for patients with inoperable ESCC in the real world and to find predictors for the efficacy of PD-1 inhibitors. Patients with unresectable ESCC were evaluated at baseline. The clinical data of patients with ESCC who received CRT/CT with or without PD-1 inhibitor were collected and retrospectively reviewed. The objective response rate (ORR), overall survival (OS), and progression-free survival (PFS) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The results of real-world and retrospective studies have also proved the superiority of immunotherapy. This point was also confirmed by the study by Wei et al [ 21 ]. After a retrospective analysis of 48 patients with recurrent or metastatic ESCC, they found that the median PFS of 29 patients receiving ICIs + CRT and 19 patients receiving ICIs + CT were 6.0 months and 5.0 months, respectively ( P = 0.025).…”
Section: Discussionsupporting
confidence: 83%
“…The results of real-world and retrospective studies have also proved the superiority of immunotherapy. This point was also confirmed by the study by Wei et al [ 21 ]. After a retrospective analysis of 48 patients with recurrent or metastatic ESCC, they found that the median PFS of 29 patients receiving ICIs + CRT and 19 patients receiving ICIs + CT were 6.0 months and 5.0 months, respectively ( P = 0.025).…”
Section: Discussionsupporting
confidence: 83%
“…The results of real-world and retrospective studies have also proved the superiority of immunotherapy. This point was also con rmed by the study by Wei et al [22]. After a retrospective analysis of 48 patients with recurrent or metastatic ESCC, they found that the median PFS of 29 patients receiving ICIs+CRT and 19 patients receiving ICIs+CT were 6.0 and 5.0 months, respectively (P = 0.025).…”
Section: Discussionsupporting
confidence: 57%
“…Wie and colleagues evaluated the addition of ICI to CRT in inoperable advanced esophageal cancer patients after first-line treatment failure in a small retrospective study. CRT plus PD-1 inhibitor was given in 26 patients and had superior OS as compared with CRT alone in 22 patients (HR 0.19, 95% CI 0.069-0.509, and p = 0.001), with similar PFS [23].…”
Section: Retrospective Studiesmentioning
confidence: 97%